The end of days (W W Norton & Co Inc, New Directions, New Directions Books, 2019)
The End of Days, by acclaimed German writer Jenny Erpenbeck, consists essentially of five "books," each leading to a different death of an unnamed woman protagonist. How could it all have gone differently? the narrator asks in the intermezzos between. The first chapter begins with the death of a baby in the early twentieth-century Hapsburg Empire. In the next chapter, the same girl grows up in Vienna, but her strange relationship with a boy leads to another death. In the next scenario, she survives adolescence and moves to Russia with her husband. Both are dedicated Communists, but our heroine is sent to a labor camp. She is spared in the next chapter with the help of someone's intervention and returns to Berlin to become a respected writer…